Clinical Implications of Nonbiological Factors With Colorectal Cancer Patients Younger Than 45 Years - Liu, Qi; Zhang, Ruoxin; Li, Qingguo; Li, Xinxiang (Frontiers in Oncology, 2021)
Background：To evaluate the real-world implications of non-biological factors (NBFs) with staging, prognosis and clinical management in colorectal cancer (CRC) patients younger than the recommended initiating CRC screening age. Methods: Univariate and multivariate Cox proportional hazard regression analyses were conducted to evaluate the prognosis of different prognostic factors, the hazard ratios (HRs) were shown with 95% confidence intervals (CIs). The Kaplan–Meier method was used to compare the prognostic value of different factors with the log-rank test. NBF score was determined according to the result of multivariate Cox analyses. Results: In total, 15129 patients before the recommended initiating CRC screening age with known NBFs were identified from the SEER database. Only county-level median household income, marital status and insurance status were NBFs that significantly corelated with the cause specifical survival in CRC patients aged less than 45 years old (P < 0.05). Stage NBF 1 was independently associated with 50.5% increased risk of CRC specific mortality (HR = 1.505, 95% CI = 1.411-1.606, P < 0.001). Stage NBF 0 patients were associated with a statistically significant increased CCSS as compared to the stage NBF 1 patients in all the respective AJCC TNM stages. Conclusions: NBF stage (defined by county-level median household income, marital status and insurance status) was strongly associated with the prognosis of patients younger than the recommended initiating CRC screening age. We strongly support the incorporation of NBF-stage into conventional AJCC TNM staging system, which is crucial for better prognostic prediction accuracy and individualized risk-adaptive therapies.